Integrative Brain Transcriptome Analysis Reveals Region-Specific and Broad Molecular Changes in Shank3-Overexpressing Mice - Jin, Chunmei; Kang, Hyojin; Ryu, Jae Ryun; Kim, Shinhyun; Zhang, Yinhua; Lee, Yeunkum; Kim, Yoonhee; Han, Kihoon (Frontiers in Molecular Neuroscience, 2018)
Variants of the SHANK3 (SH3 and multiple ankyrin repeat domains 3) gene, encoding excitatory postsynaptic core scaffolding proteins, are causally associated with numerous neurodevelopmental and neuropsychiatric disorders, including autism spectrum disorders (ASDs), bipolar disorder, intellectual disability, and schizophrenia (SCZ). Although detailed synaptic changes of various Shank3 mutant mice have been well-characterized, broader downstream molecular changes, including both direct and indirect changes, remain largely unknown. To address this issue, we performed a transcriptome analysis of the medial prefrontal cortex (mPFC) of adult Shank3-overexpressing transgenic (TG) mice, using an RNA-sequencing approach. We also re-analyzed previously reported RNA-sequencing results of the striatum of adult Shank3 TG mice and of the prefrontal cortex of juvenile Shank3+/C mice with a 50-70% reduction of Shank3 proteins. By comparing the differentially expressed genes (DEGs) of the analyses side by side, we found that several myelin-related genes were significantly down-regulated specifically in the mPFC, but not in the striatum or hippocampus, of adult Shank3 TG mice. In addition, we also found nine common DEGs between the mPFC and striatum of Shank3 TG mice, among which we further characterized ASD- and SCZ-associated Gpr85 (G protein-coupled receptor 85), encoding an orphan G protein-coupled receptor interacting with PSD-95. Unlike the mPFC-specific decrease of myelin-related genes, we found that the mRNA levels of Gpr85 increased in multiple brain regions of adult Shank3 TG mice, while the mRNA levels of its family members, Gpr27 and Gpr173, decreased in the cortex and striatum. Intriguingly, in cultured neurons, the mRNA levels of Gpr27, Gpr85, and Gpr173 were modulated by neuronal activity. Furthermore, exogenously expressed GPR85 was co-localized with PSD-95 and Shank3 in cultured neurons, and negatively regulated the number of excitatory synapses, suggesting its potential role in homeostatic regulation of excitatory synapses in Shank3 TG neurons. Lastly, we performed a gene set enrichment analysis of the RNA-sequencing results, which suggested that Shank3 could affect the directional expression pattern of numerous ribosome-related genes in a dosage-dependent manner. Together, these results reveal previously unidentified brain region-specific and broad molecular changes in Shank3-overexpressing mice, further elucidating the complexity of the molecular pathophysiology of SHANK3-associated brain disorders.